Proses Penyelesaian Sengketa Lahan Hutan: Suatu Kajian Antropologi Hukum Kasus Sengketa Lahan Hutan antara Perusahaan HPH PT. Diamond Raya Timber dengan Masyarakat Lokal di Kabupaten Bengkalis, Propinsi Riau - Didik Suharjito (Institut Pertanian Bogor (IPB University), 2001)
This study present a case of forest land dispute between Private Forestry Company and Local Community and its resolution processes. The study focus on the strategy options, implemented by interest groups. The strategies include law option (customary law, state law, letter of agreements) and conflict resolution models option (negotiation, mediation, etc). Which strategy implemented by interests groups will determine the results of the resolution process. This study describe which laws, models of resolution, and the results. The local community has chosen the letter of agreement, i.e. the forest land boundary, as the basis of (forest) land claim, while the Private Forestry Company, on the other hand, has chosen the state laws (decrees of forestry ministry). The NGOs has chosen her position as the community representative, while the government (forestry department, provincial government), on the other hand, tended to be the company agent. Neither of the local community and the NGOs or the company has satisfied yet to the result of the conflict resolution.